2019
DOI: 10.1177/1524839919858082
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Research as Applied Science: Bridging the Research to Practice Gap

Abstract: Implementation research is intended to address challenges posed by the slow adoption of evidence-based science by the medical and health promotion practice community. A case study approach is used to illustrate and discuss the use of Quality improvement and Evaluation as an applied approach to implementation science in contrast of more classic purposes of research. Quality improvement was the implementation model used to facilitate organizational change needed to adopt the use of texting to report sexually tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…10 Implementation science is the field of determining the best way to implement new guidelines and promotes the uptake of research findings into routine healthcare, including through nudge interventions. 16,17 Implementation scientists argue that thoughtful system design when implementing new guidelines is crucial to increasing uptake. 18 Simple nudge interventions are generally low-cost, require minimal resources and can be effective at changing healthcare worker behaviour.…”
Section: Improved Knowledge Translation and Building A Learning Health Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Implementation science is the field of determining the best way to implement new guidelines and promotes the uptake of research findings into routine healthcare, including through nudge interventions. 16,17 Implementation scientists argue that thoughtful system design when implementing new guidelines is crucial to increasing uptake. 18 Simple nudge interventions are generally low-cost, require minimal resources and can be effective at changing healthcare worker behaviour.…”
Section: Improved Knowledge Translation and Building A Learning Health Systemmentioning
confidence: 99%
“…Choosing Wisely found that without specific targeted education or alternative interventions, there was little change in practice despite newer recommendations 10 . Implementation science is the field of determining the best way to implement new guidelines and promotes the uptake of research findings into routine healthcare, including through nudge interventions 16,17 . Implementation scientists argue that thoughtful system design when implementing new guidelines is crucial to increasing uptake 18 …”
Section: Improved Knowledge Translation and Building A Learning Health Systemmentioning
confidence: 99%
“…With support of the Centers for Disease Control and Prevention (CDC) in 1994, SOPHE convened the first meeting of U.S. researchers in health education to develop a research agenda aimed at creating capacity to promote and maintain health (Clark & McLeroy, 1995). In addition, recognizing the gap between research and practice in public health settings, SOPHE has championed implementation science as an increasingly important field of study for improving health outcomes (Livingood et al, 2020; Lobb & Colditz, 2013). Through professional development opportunities (e.g., conferences, webinars) and its journals, SOPHE has been an important facilitator in connecting researchers and practitioners, as well as in putting in their hands new theoretical constructs and tools for applying research to practice (Perales, 2012).…”
Section: Strategic Commitmentsmentioning
confidence: 99%
“…From their nascent days, SOPHE’s journals, Health Education & Behavior ( HE&B ; formerly Health Education Monographs 1961-1982 and Health Education Quarterly , 1982-1995), Health Promotion Practice ( HPP ; launched 2000), and Pedagogy in Health Promotion: The Scholarship of Teaching and Learning (launched 2016), have advanced the theoretical, practice, and teaching foundations of the field. Today, SOPHE’s journals continue to be in the vanguard of publishing case studies and frameworks for implementing evidence-based science (Leeman et al, 2017; Livingood et al, 2020), and are leading the way in advancing the scholarship of teaching and learning for the public health workforce (Gambescia & Early, 2017).…”
Section: Strategic Commitmentsmentioning
confidence: 99%
“…LARC is a particularly appropriate challenge for Implementation Research, the science of closing the gap between research and practice, because of the disconnect between its high e cacy and low implementation by the practice community. We used the Consolidated Framework for Implementation Research (CFIR) for organizing and guiding development of Implementation Theory (7,8), as a useful framework for an applied approach to Implementation Science (9). A recent change in reimbursement policy regarding the provision of immediate postpartum LARC placement at hospitals providing obstetric care to underserved women represents a major opportunity for improving access to LARC.…”
Section: Introductionmentioning
confidence: 99%